THE ROLE AND EFFECTIVENESS OF GYMNASTICS EXERCISES IN THE PHYSICAL DEVELOPMENT OF GENERAL SECONDARY SCHOOL STUDENTS - Muqaddam Asatulla qizi Yangiboyeva (American Journals, 2025)
This scientific article examines the pedagogical, physiological, and methodological role of gymnastics exercises in the physical development of students in general secondary education. The study emphasizes that regular and methodologically grounded gymnastic activities improve strength, flexibility, balance, coordination, and posture in school-aged children. The paper analyzes both classical and modern approaches to gymnastics training, highlighting their cognitive, psychological, and health-promoting effects. The methodology integrates empirical data, literature review, and experimental modeling in school environments to evaluate the efficiency of structured gymnastics programs. Results indicate significant improvements in motor skills, muscular endurance, and overall physical fitness levels among students participating in systematic gymnastics sessions. The paper concludes with practical recommendations for educators and policymakers to integrate gymnastics more effectively into school curricula.
Keywords: Gymnastics, physical development, motor skills, secondary education, health promotion, posture, flexibility, pedagogy